(untitled) (Journal of Science and Technology, 2016)
This paper investigates the globalization of the fashion industry and its effects on Ghanaian independent fashion designers and finds feasible strategies that can be employed for the improvement of the fashion business in Ghana. The research is based on qualitative research approach which employs observation and interview for data collection. The population studied comprises fashion producers who have their workshops within twelve suburbs in Kumasi. The purposive sampling technique was utilized to select six respondents from each of the suburbs. Data collected was tabulated, interpreted and discussed. The study reveals among other things, that the Ghanaian fashion producers face serious challenges with the major one being importation of “seconds” and used clothes from Europe, America and cheap clothing and textiles from Asian countries. Lack of capital, knowledge and key skills, low and irregular income are among other challenges facing respondents. Strategies suggested for the improvement of the Ghanaian fashion business include; formation of strong alliance by all fashion producers in Ghana to influence the government to formulate policies that will address importation of fashion goods that compete unfairly with the Ghanaian fashion products, provide financial assistance in the form of loans to help in acquisition of current and more efficient machinery and raw material to improve and expand their businesses, and organise regular proficiency training for skills and competency upgrading to equip them to produce to meet international standards.